Environmental Toxin Screening Using Human-Derived 3D Bioengineered Liver and Cardiac Organoids - Forsythe, Steven D.; Devarasetty, Mahesh; Shupe, Thomas; Bishop, Colin; Atala, Anthony; Soker, Shay; Skardal, Aleksander (Frontiers in Public Health, 2018)
Introduction Environmental toxins, such as lead and other heavy metals, pesticides, and other compounds, represent a significant health concern within the USA and around the world. Even in the twenty-first century, a plethora of cities and towns in the U.S. have suffered from exposures to lead in drinking water or other heavy metals in food or the earth, while there is a high possibility of further places to suffer such exposures in the near future. Methods We employed bioengineered 3D human liver and cardiac organoids to screen a panel of environmental toxins (lead, mercury, thallium, and glyphosate), and charted the response of the organoids to these compounds. Liver and cardiac organoids were exposed to lead (10 µM–10 mM), mercury (200 nM–200 µM), thallium (10 nM–10 µM), or glyphosate (25 µM–25 mM) for a duration of 48 h. The impacts of toxin exposure were then assessed by LIVE/DEAD viability and cytotoxicity staining, measuring ATP activity and determining IC50 values, and determining changes in cardiac organoid beating activity. Results As expected, all of the toxins induced toxicity in the organoids. Both ATP and LIVE/DEAD assays showed toxicity in both liver and cardiac organoids. In particular, thallium was the most toxic, with IC50 values of 13.5 and 1.35 µM in liver and cardiac organoids, respectively. Conversely, glyphosate was the least toxic of the four compounds, with IC50 values of 10.53 and 10.85 mM in liver and cardiac organoids, respectively. Additionally, toxins had a negative influence on cardiac organoid beating activity as well. Thallium resulting in the most significant decreases in beating rate, followed by mercury, then glyphosate, and finally, lead. These results suggest that the 3D organoids have significant utility to be deployed in additional toxicity screening applications, and future development of treatments to mitigate exposures. Conclusion 3D organoids have significant utility to be deployed in additional toxicity screening applications, such as future development of treatments to mitigate exposures, drug screening, and environmental toxin detection.